X-ray spectroscopic analysis of Liesegang patterns in Mn–Fe-based Prussian blue analogs. Issue 8 (12th July 2016) - Hayashi, Hisashi; Abe, Hitoshi
Abstract : We performed time-resolved X-ray fluorescence (XRF) and position-dependent X-ray absorption near-edge structure (XANES) measurements on Liesegang patterns in Mn–Fe-based Prussian blue analogs. Abstract : We performed time-resolved X-ray fluorescence (XRF) and position-dependent X-ray absorption near-edge structure (XANES) measurements on gels containing Mn 2+ and [Fe(CN)6 ] 3− ions. A sample tube containing an agar gel mixed with 0.20 M MnCl2 solution and a water-glass gel mixed with 0.25 M K3 [Fe(CN)6 ] solution was prepared for these X-ray spectroscopic analyses. Periodic bands that obeyed the empirical scaling laws characteristic of Liesegang bands formed beyond the turbid zone in the water-glass gel. XRF results demonstrated that the turbid zone and the periodic bands contained diffusive Mn and Fe compounds. XANES results indicated that the Fe local structure in the sample tube was nearly independent of positions and was predominantly [Fe(CN)6 ]. In contrast, the Mn local structure depended on the position. FEFF calculations suggested that Mn–Fe-based Prussian blue analogs, of which the most likely local structure is [Mn(NCFe)3 O3 K3 ], co-existed with [MnO6− n Cl n ] ( n = 0, 1) species and that their compositions were position-dependent.